Internal C–C Bond Rotation in Photoisomers of α‐Bisimines: a Light‐Responsive Two‐Step Molecular Speed Regulator Based on Double Imine Photoswitching. Issue 7 (12th February 2016) - Greb, Lutz; Eichhöfer, Andreas; Lehn, Jean‐Marie
Abstract: Benzil‐based α‐bisimines are implemented as photoswitches for the construction of a speed‐regulating molecular device, in which, by application of light, three different states may be addressed, showing distinct frequencies of internal C–C bond rotation, spanning 12 orders of magnitude. Bond rotation barriers were determined experimentally and elucidated by DFT‐methods. Abstract : Benzil based α‐bisimines are implemented as photoswitches for the construction of a speed‐regulating molecular device. By application of light, three different states with distinct frequencies of internal C–C bond rotation may be addressed, spanning 12 orders of magnitude.